After we fell [videorecording (DVD)] - Gibgot, Jennifer; Soboil, Sharon; Langford, Josephine, 1997-; Fiennes-Tiffin, Hero; Perdomo, Chance; Lombard, Louise, 1970-; Todd, Anna (Vertical, 2022)
Just as Tessa makes the biggest decision of her life, everything changes. Revelations about her family, and then Hardin's, throw everything they knew before in doubt and makes their hard-won future together more difficult to claim.